Teacher Persuasive Communication in Improving Discipline of Autistic Children at SLBIT Sahabat Al-Qur'an Binjai - Alsha Naumi; Dika Sahputra (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to describe the role of teacher persuasive communication in improving the discipline of autistic children at SLBIT Sahabat Al-Qur'an Binjai. This study uses a qualitative descriptive method, with data collection techniques in the form of observation, interviews, and documentation. This study examines how teachers use persuasive communication with the AIDDA (Attention, Interest, Desire, Decision, Action) approach. The main informants in this study were 2 teachers and 2 autistic children who were the research samples. The results of the study showed that the teacher's approach that was adjusted to the characteristics of each child played an important role in building discipline. Despite facing various challenges, effective and consistent communication succeeded in motivating autistic children to follow the rules and procedures that had been set.